Feasibility of proton FLASH effect tested by zebrafish embryo irradiation - Beyreuther, Elke; Brand, Michael; Hans, Stefan; Hideghéty, Katalin; Karsch, Leonhard; Leßmann, Elisabeth; Schürer, Michael; Szabó, Emília Rita; Pawelke, Jörg (Radiotherapy and oncology, 2019)
BACKGROUND AND PURPOSE: Motivated by first animal trials showing the normal tissue protecting effect of electron and photon Flash irradiation, i.e. at mean dose rates of 100Gy/s and higher, relative to conventional beam delivery over minutes the feasibility of proton Flash should be assessed. - MATERIALS AND METHODS: A setup and beam parameter settings for the treatment of zebrafish embryo with proton Flash and proton beams of conventional dose rate were established at the University Proton Therapy Dresden. Zebrafish embryos were treated with graded doses and the differential effect on embryonic survival and the induction of morphological malformations was followed for up to four days after irradiation. - RESULTS: Beam parameters for the realization of proton Flash were set and tested with respect to controlled dose delivery to biological samples. Analyzing the dose dependent embryonic survival and the rate of spinal curvature as one type of developmental abnormality, no significant influence of proton dose rate was revealed. For the rate of pericardial edema as acute radiation effect, a significant difference (p<0.05) between proton Flash and protons delivered at conventional dose rate of 5Gy/min was observed for one dose point only. - CONCLUSION: The feasibility of Flash proton irradiation was successfully shown, whereas more experiments are required to confirm the presence or absence of a protecting effect and to figure out the limits and requirements for the Flash effect.